2003
DOI: 10.1590/s1413-70542003000500012
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade morfocultural e genética de fungos associados a podridão peduncular do mamão

Abstract: RESUMO -Objetivou-se, com este trabalho, verificar a variabilidade morfocultural e genética de fungos associados à podridão peduncular do mamão (Carica papaya L. MORPHOCULTURAL AND GENETIC VARIABILITY OF FUNGI ASSOCIATED WITH STEM-END ROT OF PAPAYAABSTRACT -The objective of this work was to look at the variability between isolates of the three fungal species, Colletotrichum gloeosporioides, Fusarium solani and Phoma caricae-papayae associated with stem-end rot in papaya fruits (Carica papaya L.) which were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
9
0
6
Order By: Relevance
“…In the following evaluations the colonies in UV-C treatments had already recovered and were developing normally and had an appearance equivalent to that of control. In addition, regression analysis between the mycelial growth index calculated according to Peres et al (2003) and UV-C doses did not show a correlation (data not shown), indicating that UV-C do not significantly influence G. citricarpa mycelial growth.…”
Section: In Vitro Effect Of Uv-c Irradiation On G Citricarpa Developmentioning
confidence: 92%
“…In the following evaluations the colonies in UV-C treatments had already recovered and were developing normally and had an appearance equivalent to that of control. In addition, regression analysis between the mycelial growth index calculated according to Peres et al (2003) and UV-C doses did not show a correlation (data not shown), indicating that UV-C do not significantly influence G. citricarpa mycelial growth.…”
Section: In Vitro Effect Of Uv-c Irradiation On G Citricarpa Developmentioning
confidence: 92%
“…The collected data was used to calculate the MGR (mycelial growth rate), as demonstrated by Peres et al (2003), according to the mathematical equation: determination of peel and pulp color, a colorimeter Hunter Lab -MiniScan XE Plus, L C °H system [L represents luminance, C represents chroma, and °H (Hue), the color angle (0° to 360° -0°: Red; 90°: yellow; 180°: green; and 270°: blue)], with readings in two opposite points in the equatorial region of the fruit; Soluble solids content was determined with the fruit juice, obtained by the centrifugation of two fruit per repetition, directly read in a digital refractometer Pal -1 (Atago®), and the results were expressed in °Brix; Titratable acidity was determined by titration, with sodium hydroxide solution (NaOH) 0.1 N until pH 8.10 (pH meter Digimed®), using 10 g of juice, diluted in 90 mL of distilled water. The results were expressed as percentage citric acid.…”
Section: Methodsmentioning
confidence: 99%
“…A baixa atividade apresentada pode indicar que a celobiose, na concentração utilizada, teria reprimido a ação enzimática extracelular, sendo esse substrato hidrolizado pela enzima celobiase intracelular, levando ao acúmulo de glicose que age como repressor enzimático (Mandels e Reese, 1960). A produção de ß-glucosidase in vitro também já foi relatada por Peres et al (2000) para Fusarium, Ascochyta e Colletotrichum e por Kader e Omar (1998), que observaram a produção da enzima por três espécies de Aspergillus e duas de Trichoderma, quando cultivadas em meios de cultivo suplementados com carboximetilcelulose.…”
Section: Atividade Enzimática In Vitrounclassified